Human liver sinusoidal endothelial cells promote intracellular crawling of lymphocytes during recruitment: A new step in migration. Issue 1 (25th November 2016) - Patten, Daniel A.; Wilson, Garrick K.; Bailey, Dalan; Shaw, Robert K.; Jalkanen, Sirpa; Salmi, Marko; Rot, Antal; Weston, Chris J.; Adams, David H.; Shetty, Shishir
Abstract : The recruitment of lymphocytes via the hepatic sinusoidal channels and positioning within liver tissue is a critical event in the development and persistence of chronic inflammatory liver diseases. The hepatic sinusoid is a unique vascular bed lined by hepatic sinusoidal endothelial cells (HSECs), a functionally and phenotypically distinct subpopulation of endothelial cells. Using flow‐based adhesion assays to study the migration of lymphocytes across primary human HSECs, we found that lymphocytes enter into HSECs, confirmed by electron microscopy demonstrating clear intracellular localization of lymphocytes in vitro and by studies in human liver tissues. Stimulation by interferon‐γ increased intracellular localization of lymphocytes within HSECs. Furthermore, using confocal imaging and time‐lapse recordings, we demonstrated "intracellular crawling" of lymphocytes entering into one endothelial cell from another. This required the expression of intracellular adhesion molecule‐1 and stabilin‐1 and was facilitated by the junctional complexes between HSECs. Conclusion: Lymphocyte migration is facilitated by the unique structure of HSECs. Intracellular crawling may contribute to optimal lymphocyte positioning in liver tissue during chronic hepatitis. (Hepatology 2017;65:294‐309).